Organic agricultural products in Europe and USA = Organiczne produkty rolnicze w Europie i USA - Skrodzka, Violetta (Zielona Góra: Faculty of Economics and Management Press)
In the most developed countries of Western Europe and North America, the share of organic farming in the food market is between 2% and 6%. The share of organic products on the Polish food market is only 0.33% (Dryjańska E. 2017). The aim of this article is to compare organic agricultural products in the US and EU. The scope of the comparison was covered by the legal regulations for organic production in the mentioned regions and the availability of organic products for customers.
Keywords: produkty ekologiczne; żywność ekologiczna; normy produktów ekologicznych; badania nad żywnością ekologiczną; organic product; organic food; ecological products standards; research on organic food